Plan de exportación de camisetas para el posicionamiento estratégico de la empresa Derick en Costa Rica - Ruiz, José G. (2021)
Ecuador is a country that presents several opportunities for its producers, in recent years it has gained an international market, due to its geographical location it presents several benefits in the same way it has maritime ports that are strategic when conducting international trade, so it allows to be a developing country and at the same time competitive. The purpose of this research work is to design a plan for the export of t-shirts, for the Derick company, to the Costa Rican market, which will serve as a support and guide document, with a main objective that the company has competitiveness and can expand its commercialization internationally.